O Azulejo saiu da parede - Menezes, Marluci (Trabalhos de Antropologia e Etnologia, 2020)
The Azulejo is out of the Wall. Based on an exploratory research, this article discusses some contemporary aspects of the patrimonialization of the azulejo. The institutionalization of the internet in the diffusion of the azulejo heritage and the tendency for an increase in the dissemination of glazed ceramics integrated in architecture is pointed out, as well as the irruption of its utilization in urban art, in fashion and various consumption goods. It also notes the increase of online condemning of azulejo heritage destruction, namely that integrated in architecture. The research carried out so far also allows to emphasize some aspects to be discussed in future developments: the tendency for the current assumption that the tile heritage is also associated with the transformation of azulejos into materials and meanings other than wall linings in architecture; the current role of the online effect for the dissemination of the azulejo as heritage is a manifestation that assumes various and different supports; its transnational dissemination as a mark of Portuguese national culture; the use of azulejo designs on other materials can contribute to diffuse and thus protect the azulejo heritage, but can also lead to the dematerialization of the tile heritage itself. In both cases, the online repercussions are to be noted. We point out the potential of online research in the field of heritage and, finally, some of its limitations are discussed, namely for placing the researcher away from the social territories of the heritage itself.